On-farm performance evaluation of Maale goats under agro-pastoral management in Southwest Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2023)
This study was conducted in Maale district Southwest Ethiopia with the objective of evaluating the productive and reproductive performance of Maale goats under agro-pastoral management conditions. Thirty households that have flocks numbers of more than ten were purposely selected and monitored from July 2018 to July 2019. Growth data of birth weight, three month, six month, nine month and yearly weight; birth type and parity were collected. The data were analyzed using the General Linear Model (GLM) procedure of SPSS (21). The overall mean birth weight of the kids was 2.57±0.05 kg (males 2.68±0.07 and females 2.47±0.07 kg). The weaning and six months weight of kids was significantly different (p